The Scout Education Management of (Senior Scouts) - Munawwarah, Tarisa; Sani, Dinda Aulia; Kholizah, Nur Alfiana; Hanifah, Fathia; Savitri, Intan; Budi, Budi (The Future of Education Journal, 2024)
This research discusses the management of scouting education at the scout junior level using the literature review research method. The scout junior level refers to scouts aged 11 to 15 years, who play an important role in shaping the character of the youth through structured and tiered activities. The management of scouting education at this level includes the organization of patrols, the implementation of the scout code of honor, and various activities such as jamborees, competition events, patrol leader training, and exploration. Literature studies show that scouting methods, including group-based activities, cooperation, and competition, are effective in developing leadership skills, teamwork, and independence. This research emphasizes that the management of scouting education at the junior scout level plays a crucial role in character development based on moral values, discipline, and responsibility, which are essential for addressing the challenges faced by youth in the modern era.